Two new genera of Pacific Paraboloponina leafhoppers (Hemiptera: Cicadellidae: Drabescini) with description of three new species - Lu, Lin; Dietrich, Christopher H.; Webb, M. D.; Zhang, Yalin (Zootaxa, 2019)
Two new genera, Malaysiapona gen. nov. and Chandrapona gen. nov. of Paraboloponina leafhoppers (Cicadellidae: Deltocephalinae: Drabescini) with their unusally developed aedeagal base are described from the Pacific (Malaysia). The following new species are also described with the new genera: Malaysiapona brevipenis sp. nov. from Sabah, M. filamenta sp. nov., from Sarawak and Chandrapona vespertilis sp. nov. from Sabah.